Credit composition and housing price dynamics: a disaggregation approach. Issue 11 (24th July 2022) - Duan, Kun; Parhi, Mamata; Wolfe, Simon
Abstract : While credit plays an instrumental role in housing price dynamics, existing work has produced conflicting evidence of its real impact. This paper reconciles various inconclusive findings via a disaggregation strategy to decompose aggregate credit into credit-to-the-real economy ( cr ) and credit-to-the-asset markets ( cf ). We argue that these two credit components exert theoretically expected and distinct impacts on housing prices, identified separately through a housing demand and a housing supply credit-circulation channel. Using an international panel dataset and treating for periodic cycles, our panel VAR estimations show that cr and housing prices depict a mutually reinforcing positive relationship. However, cf exerts a negative but negligible impact on housing prices in the short-run; it has a strong and positive effect in the long-run. Further, controlling for effects of economic policy uncertainty strengthens the interactions between housing prices and the two credit components. Our results are robust and suggest that close monitoring of credit allocation to housing demand and supply sides, as well as the extent of pump-priming resource allocation to the real economy, should be of interest to policymakers.